16.6k views
4 votes
HELP !!!! look at the picture

HELP !!!! look at the picture-example-1
User Weetu
by
4.9k points

1 Answer

5 votes

Answer:

Option C:

g(x) = -3^x

Explanation:

Here we can see the graphs of f(x) and the graph of g(x).

By only looking at that, we can see that g(x) is a reflection across the x-axis of f(x).

Remember that for a general function f(x), the reflection across the x-axis is written as:

g(x) = -f(x).

Then, if f(x) = 3^x

and g(x) = -f(x)

replacing f(x) we get:

g(x) = -(3^x) = -3^x

The correct option is C.

User Renato Stauffer
by
5.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.